2022
DOI: 10.1071/zo21023
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and cross-amplification of sex-specific genetic markers in Australasian Egerniinae lizards and their implications for understanding the evolution of sex determination and social complexity

Abstract: Sex is a pervasive factor that underpins functional phenotypic variation across a range of traits. Although sex can usually be distinguished morphologically, in some species this is not possible. The development of genetic markers for sex identification is, thus, key if we are to incorporate sex into an understanding of ecological or evolutionary process. Here we develop genetic markers for the identification of sex within an iconic Australian lizard group, the Egernia group, which is notable for its complex s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…The amplification of several of our sexing markers across four other Carinascincus species suggest that the sex determining system of C. ocellatus is shared across the genus. However, the fact that all markers failed in two more distantly related skinks casts doubt on the conservation of sex determination across all Scincidae, as previously suggested based on work in the Egernia subfamiliy and in the ground skink Scincella melanostica 25,50 . Testing the PCR markers developed here and by others 25,44,51 across a larger panel species would benefit our understanding of scincid lizard sex chromosome evolution.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…The amplification of several of our sexing markers across four other Carinascincus species suggest that the sex determining system of C. ocellatus is shared across the genus. However, the fact that all markers failed in two more distantly related skinks casts doubt on the conservation of sex determination across all Scincidae, as previously suggested based on work in the Egernia subfamiliy and in the ground skink Scincella melanostica 25,50 . Testing the PCR markers developed here and by others 25,44,51 across a larger panel species would benefit our understanding of scincid lizard sex chromosome evolution.…”
Section: Discussionmentioning
confidence: 89%
“…However, the fact that all markers failed in two more distantly related skinks casts doubt on the conservation of sex determination across all Scincidae, as previously suggested based on work in the Egernia subfamiliy and in the ground skink Scincella melanostica 25,50 . Testing the PCR markers developed here and by others 25,44,51 across a larger panel species would benefit our understanding of scincid lizard sex chromosome evolution. More broadly, our study highlights the benefits of increasing the number of available sex-linked genetic markers and molecular sexing tests in taxonomic groups with poorly studied sex determination.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Over 70% of transcripts assembled here aligned to the wall lizard genome, despite an estimated divergence time of 174 Myr ( Kumar et al 2017 ). In contrast, alignment of raw RRS reads (usually done with Blast) tends to have poor success when no close reference genome is available (1% to 10%; Brelsford et al 2017 ; Nielsen et al 2019 , 2020 ; Keating et al 2022 ; Bouffet-Halle et al 2022 ). In C. ocellatus , a previous RRS study identified ∼300 sex-linked markers of which only 2% aligned to Blast's nucleotide collection ( Hill et al 2018 ; Cornejo-Páramo et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%